A systematic review of measurements of service quality and consumer experience - Klaus, Philipp (Cranfield University, 2007)
The challenge of predicting consumer behaviour is widely considered by the literature as a rather daunting, but worthwhile task. Which manager or academic would not be interested in using or developing a framework enabling one to predict future behaviour better than existing measurements? Refering to the old saying, stating that ‘only what gets measured, gets managed’, indicating what the literature addresses as a need to track the influence of change through measurements. In order to address my research question and explore the proposition ‘Can a measurement of service quality based on consumer experience be a better predictor of consumer behaviour?’ this paper examines the existing literature in two fields of literature. On the one hand I will be investigating studies in the context of existing measurements of service quality to assess the first part of my research question to determine the ‘status quo’, application and characteristics of the literature on measurements of service quality. On the other hand the paper will select, appraise, and synthesize the relevant literature on consumer behaviour to address the second part of the research question, if, and if yes, how the phenomenon of consumer experience could be the foundation for a measurement of service quality capable of predicting consumer behaviour better than existing measurements of service quality. By systematically reviewing the existing literature I am aiming on contributing to the literature addressing the challenges of predicting consumer behaviour.